Design & Application of Computer Controlled Switch (Journal of Nepal Physical Society, 2017)
A parallel port is an inexpensive and powerful tool for controlling the real world peripherals. It provides eight Transistor Transistor Logic (TTL) outputs, fives inputs and four bidirectional input and output for Personal Computer (PC) interruption. By using the structure oriented programming language they are fused in circuit boards, microcontrollers etc. to carry out specified functions. The reason is the elegance and simplicity of the code used in visual basic.Journal of Nepal Physical SocietyVolume 4, Issue 1, February 2017, Page: 97-100